2010
DOI: 10.1002/elan.201000505
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Speciation of Antimony(III and V) in Water by Adsorptive Cathodic Stripping Voltammetry Using the 4‐(2‐Thiazolylazo) – Resorcinol

Abstract: A simple adsorptive cathodic stripping voltammetry method has been developed for antimony (III and V) speciation using 4-(2-thiazolylazo) -resorcinol (TAR). The methodology involves controlled preconcentration at pH 5, during which antimony(III) -TAR complex is adsorbed onto a hanging mercury drop electrode followed by measuring the cathodic peak current (I p,c ) at À0.39 V versus Ag/AgCl electrode. The plot of I p,c versus antimony(III) concentration was linear in the range 1.35 10 À9 -9.53 10 À8 mol L À1.The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
3
1
1
Order By: Relevance
“…These are summarized in Table 3. As can be seen from this table, the value of LOD is lower than most of the reported electrochemical methods [15,16,[21][22][23]26,[31][32][33]36,[38][39][40]43,45,49,52]. Moreover, the results of the interference studies showed that the selectivity of the proposed method is quite high.…”
Section: Comparison Of Proposed Methods With Other Methodscontrasting
confidence: 42%
See 3 more Smart Citations
“…These are summarized in Table 3. As can be seen from this table, the value of LOD is lower than most of the reported electrochemical methods [15,16,[21][22][23]26,[31][32][33]36,[38][39][40]43,45,49,52]. Moreover, the results of the interference studies showed that the selectivity of the proposed method is quite high.…”
Section: Comparison Of Proposed Methods With Other Methodscontrasting
confidence: 42%
“…Many voltammetric studies, including stripping methods for determination of antimony, have focused on the modification of the electrode surface or use of a chelating/complexing agent to increase the detection limit. With this aim, different complexing reagents such as catechol [33,44], chloranilic acid [34,36], morin [35], gallocyanine [37], pyrogallol red [38], pyrogallol [39,41,42], alizarin red S [40], 4-(2-thiazolylazo)-resorcinol [43], quercetin [45], and quercetin-5 -sulfonic acid [46] have been successfully used for determination of Sb(III) on a mercurybased electrode. Recently, carbon-based electrodes have attracted attention in electroanalytical studies as an attractive alternative to mercury electrodes in stripping analysis due to their many advantages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A preocupação com este compartimento ambiental é significativa, devido aos possíveis riscos aos quais organismos aquáticos estão expostos. 33,34,[37][38][39][40][41][42][43] No mesmo sentido, alguns trabalhos também avaliaram a presença de metais em águas de torneira e água envasada. [44][45][46][47][48][49] Arab and Alshikh avaliaram a presença de Cd, Cu, Fe, Pb Zn, Se em amostras de águas de torneira de diferentes pontos da cidade de Jeddah na Arábia Saudita, durante um ano empregando voltametria de redissolução por pulso diferencial e HMDE como eletrodo de trabalho.…”
Section: Determinação De íOns Metálicos Usando O Hmdeunclassified